Cadastro Único e a crise da maior idade: Quest\~oes prementes para consolidar a maturidade dessa política na era digital - Denise do Carmo Direito; Elaine Cristina Licio; Claudia Baddini Curralero (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The aim of this text is to contribute to the discussion on the growing adoption of new communication and information technologies (ICTs) in public policies. To do so, we have analyzed possible paths for the integration of one of the most relevant policies to combat hunger and exclusion: the Cadastro Único para programas sociais (Unified Registry for Social Programs). The first twenty years of the Cadastro Unico's history was marked by the expansion of this social registry and, consequently, the recognition of various dimensions of poverty affecting part of the Brazilian population. The increase in complexity, both federative and intersectoral, is a characteristic of this period. However, despite being a computerized database, it still does not offer the possibility, for example, of data collection through the internet and applications. The text provides a brief history and characteristics of the Cadastro Único. Throughout the analysis, the Brazilian solution is compared with models of social registries existing in other countries, when it's analyzed possibilities and limits. Then, in a didactic manner, the different phases of the registration process - access, data collection, and data processing - are subdivided, indicating the current uses of ICTs at each stage and the possibilities for expansion or adaptation. The conclusion addresses the possibilities of advancing in this digital transformation agenda, considering theories of change in public policies and the mechanisms in order to contribute to its adaptation to the digital era, ensuring also results in improve social services to the population and the reduction in social vulnerabilities.
Keywords: O35; 330; digital transformation; change in public policies; Cadastro Único; unified registry